Comparison of carbon content in soil and biomass in various types of sub-optimal dryland use in Aceh Besar, Indonesia. Issue 1 (1st December 2022) - Sufardi, S; Syafruddin, S; Arabia, T; Khairullah, K; Umar, HA
Abstract: This study was conducted to compare the content of carbon in soil and in biomass vegetation in various types of sub-optimal dryland in Aceh Besar district, Indonesia. Soil samples were collected from seven soil depths from 0 to 100 cm under 12 land uses including primary forest, secondary forest, pine forest, Eucalyptus forests, teak forest, forest shrubs, shrublands, and grasslands, mixed gardens, moorlands, rainfed rice fields, and bare lands. The measurement of plant biomass is differentiated according to the type of vegetation based on the BSN (2020) procedure [1]. The biomass of vegetations used allometric equations. The results of the study showed that the C content of the soil at a depth of 0-30 cm was higher than the C content at 30-100 cm. Carbon soil potential at the depth of 0-100 cm and biomass carbon contents in the sub-optimal dryland of Aceh Besar varies greatly between land-use types. The primary forest has the highest potential for soil carbon and biomass carbon compared to other land-use types. Soil and biomass C potentials in the primary forest were 332.28 ± 28.75 t ha -1 and 241.71 ± 24.46 t ha -1 (70.4%), respectively, with soil C stock of 25, 103.68 Gg. The lowest soil C potential was found in bare land, namely 57.54±5.87 t ha -1 with a biomass C potential of 0.53 ±0.06 t ha -1, while the lowest soil C stock was found in the teak forest, which was 4.83 Gg. There is a positive correlation between soil C stock and biomass C content. The ratio of soil C and biomass C in the sub-optimal dryland of Aceh Besar varied from 0.01 to 1.57.